The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1537-2995.2006.01148.x
|View full text |Cite
|
Sign up to set email alerts
|

The transfusion of neutrophil‐specific antibodies causes leukopenia and a broad spectrum of pulmonary reactions

Abstract: Neutrophil antibodies cause a wide variety of transfusion reactions that do not necessarily meet the definition of TRALI. Donors of blood products causing even mild pulmonary reactions or leukopenia should be tested for neutrophil-specific antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 18 publications
1
40
0
Order By: Relevance
“…We have had a similar experience. 84 TRALI has been observed after transfusion of most plasmacontaining blood components. The single exception appears to be pooled solvent detergent-treated plasma, in which the manufacturing process may dilute even high-titer antibodies present in any single unit.…”
Section: Transfusion-related Acute Lung Injurymentioning
confidence: 99%
“…We have had a similar experience. 84 TRALI has been observed after transfusion of most plasmacontaining blood components. The single exception appears to be pooled solvent detergent-treated plasma, in which the manufacturing process may dilute even high-titer antibodies present in any single unit.…”
Section: Transfusion-related Acute Lung Injurymentioning
confidence: 99%
“…6,10,14 These data are to be expected if one examines human alloimmune neutropenia in which maternal antibodies cross the placenta and immunodeplete the PMNs in the fetus or following transfusion of donor antibodies that bind to the PMNs of the recipient and cause immunodepletion, termed transfusion-related alloimmune neutropenia (TRAIN). [53][54][55] Alloimmune neutropenia is dependent upon the type of the antibody or the antigen recognized. Antibodies that prime PMNs through antigen recognition (eg, induce a proinflammatory change) may lead to TRALI and not antibody-mediated clearance, as shown in the presented model.…”
mentioning
confidence: 99%
“…7,20,21 The higher fatality association was demonstrated in a study by Reil et al, who reported 36 TRALI cases, 12 of which were attributable to HNA antibodies (Table 1). 7 Of these, 10 were attributable to HNA-3a antibodies, and 6 of the 10 cases were fatal.…”
Section: Hna-3a Antibodies and Tralimentioning
confidence: 82%